Ex vivo blockade of PI3K gamma or delta signaling enhances the antitumor potency of adoptively transferred CD8+ T cells. Issue 9 (28th May 2020) - Dwyer, Connor J.; Arhontoulis, Dimitrios C.; Rangel Rivera, Guillermo O; Knochelmann, Hannah M.; Smith, Aubrey S.; Wyatt, Megan M.; Rubinstein, Mark P.; Atkinson, Carl; Thaxton, Jessica E.; Neskey, David M.; Paulos, Chrystal M.
Abstract: Adoptive T cell transfer therapy induces objective responses in patients with advanced malignancies. Despite these results, some individuals do not respond due to the generation of terminally differentiated T cells during the expansion protocol. As the gamma and delta catalytic subunits in the PI3K pathway are abundant in leukocytes and involved in cell activation, we posited that blocking both subunits ex vivo with the inhibitor IPI‐145 would prevent their differentiation, thereby increasing antitumor activity in vivo. However, IPI‐145 treatment generated a product with reduced antitumor activity. Instead, T cells inhibited of PI3Kγ (IPI‐549) or PI3Kδ (CAL‐101 or TGR‐1202) alone were more potent in vivo. While T cells coinhibited of PI3Kγ and PI3Kδ were less differentiated, they were functionally impaired, indicated by reduced production of effector cytokines after antigenic re‐encounter and decreased persistence in vivo. Human CAR T cells expanded with either a PI3Kγ or PI3Kδ inhibitor possessed a central memory phenotype compared to vehicle cohorts. We also found that PI3Kδ‐inhibited CARs lysed human tumors in vitro more effectively than PI3Kγ‐expanded or traditionally expanded CAR T cells. Our data imply that sole blockade of PI3Kγ or PI3Kδ generates T cells with remarkable antitumor properties, a discovery that has substantial clinical implications. Abstract : Current expansion protocols generate T cells yields with reduced antitumor immunity. We demonstrate that incorporation of PI3K or PI3K inhibitors during expansion generates more therapeutic T cell products against solid tumors. Yet, co‐blockade of both PI3K and PI3K ex vivo generated T cells that were less effective in vivo.